1999
DOI: 10.2190/4p4y-3lyp-p5bx-t22e
|View full text |Cite
|
Sign up to set email alerts
|

China's “Market Economics in Command”: Footwear Workers' Health in Jeopardy

Abstract: This study of occupational safety and health (OSH) problems in the footwear industry in China, the world's largest shoemaker, is based on four years of research in China supplemented by research in Taiwan, Australia, and the United States. With the advent of the economic reforms of the early 1980s, the Chinese state is being driven by an economic imperative under which the profit motive overrides other concerns, causing a deterioration in OSH conditions. Footwear workers are being exposed to high levels of ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…Workers either have to work in extreme conditions or with dangerous materials. Labour injuries happen frequently (Chen and Chan, 1999).…”
Section: Working Conditionsmentioning
confidence: 99%
“…Workers either have to work in extreme conditions or with dangerous materials. Labour injuries happen frequently (Chen and Chan, 1999).…”
Section: Working Conditionsmentioning
confidence: 99%
“…Organic solvents are widely used around the world and many different industrial processes require their use. Millions of persons are currently exposed to solvents in their workplaces [2], mostly in developing countries. One of the first reports of the adverse effects of solvents on human hearing came from Szulck-Kuberska et al [3] who studied a group of workers exposed to trichloroethylene.…”
Section: Introductionmentioning
confidence: 99%
“…Millions of persons are currently exposed to solvents in their workplaces. 10 One of the first reports on the adverse effects of solvents on human hearing comes from Szulck-Kuberska et al, 11 who studied a group of workers exposed to trichloroethylene. Animal studies have found cochlear damage due to aromatic solvent exposure.…”
mentioning
confidence: 99%